Effects of raw and roasted high oleic soybeans on milk production of high-producing dairy cows - A.M. Bales; A.L. Lock (Journal of Dairy Science)
ABSTRACT: Processing method of soybeans has the potential to influence dairy cow production performance; therefore we determined the effect feeding raw or roasted ground soybeans high in oleic acid (HOSB) on production responses of high-producing dairy cows. Thirty-six multiparous Holstein cows (45.6 ± 6.22 kg/d of milk; 110 ± 61 DIM) were randomly assigned to treatment sequences in a 4 × 2 truncated Latin square design with 35-d periods. Treatments were as follows: (1) control diet, containing soybean meal and soybean hulls (CON); (2) 16% roasted and ground HOSB (RST); (3) 16% raw and ground HOSB (RAW-D); and (4) 16% raw and ground HOSB + additional rumen bypass protein (RAW-U). The HOSB replaced conventional soybean meal and hulls in the control diet, and rumen bypass protein replaced soybean meal in RAW-U to maintain diet nutrient composition (% DM) of ∼28.0% NDF, 21.3% forage NDF, 27.3% starch, and 17.8% CP. Fatty acid contents of CON, RST, RAW-D, and RAW-U were 1.60, 4.30, 4.36, and 4.34% DM, respectively. Preplanned contrasts included the overall effect of HOSB inclusion (CON vs. HOSOY [1/3 {RST + RAW-D + RAW-U}]), the effect of soybean processing (RST vs. raw treatments [1/2 {RAW-D + RAW-U}]), and the effect of increasing RUP content within the raw HOSB treatments (RAW-D vs. RAW-U). For most variables tested, significant interactions between treatment and week occurred, as HOSOY increased production variables compared with CON, and RST increased production responses compared with raw treatments, with only the magnitude of difference varying between weeks. Overall, HOSOY increased DMI and yields of milk, 3.5% FCM, ECM, and milk fat, but did not affect milk protein yield. The RST treatment did not affect DMI but increased yields of milk, 3.5% FCM, ECM, milk fat, and milk protein. Compared with RAW-D, RAW-U increased yields of milk and milk protein and tended to increase ECM. Overall, HOSB inclusion of 16% DM increased production responses in high-producing dairy cows, but roasted HOSB had a greater effect than raw HOSB, and the addition of rumen bypass protein positively affected milk protein response.